1,5-Anhydroglucitol als Marker kurzfristiger Blutzuckerspitzen = 1,5-anhydroglucitol as a marker for short-term glycaemic excursions - Kulozik, Felix; Hasslacher, Christoph (Diabetes, Stoffwechsel und Herz, 2015)
Background: The development of vascular diabetic complications depends on HbA1c levels as well as intermittent hyperglycaemic states. 1, 5-anhydroglucitol (1, 5-AG) is an established marker for short-term glycaemic excursions; the aim of this study was to analyse the correlation between 1, 5-AG and HbA1c as well as antidiabetic therapy. Methods: We analysed 1, 5-AG levels using an enzymatic test (GlycoMark®) alongside other parameters in 377 outpatients with type 2 diabetes. Results: 1, 5-AG decreased in correlation with increasing HbA1c levels. After classifying HbA1c levels into groups, a third of the patients with HbA1c < 6.5% and half of the patients with HbA1c 6.5-7.5 % showed significantly reduced levels of 1, 5-AG (≤ 5 μg/ml). Almost all of the patients with HbA1c >8.5% showed 1, 5-AG levels ≤ 5μg/ml. Conclusion: Measuring 1, 5-AG is an uncomplicated alternative to frequent postprandial and intermittent blood glucose (self) measurement or continuous glucose monitoring in addition to routine HbA1c testing in identifying type 2 diabetes patients with intermittent hyperglycaemia despite favourable HbA1c levels.
Gesehen am 05.04.2018